Біологічні основи розмноження самшиту вічнозеленого Buxus Sempervirens L. в умовах закритого ґрунту - Машевська, Алла Степанівна; Єрмейчук, Тамара Музаффарівна; Mashevska, Alla S.; Yermeichuk, Tamara M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Наведено результати дослідження регенераційної здатності самшиту вічнозеленого в умовах закритого ґрунту, визначено способи регенерації органів у процесі укорінення, експериментально перевірено вплив ростових речовин на їх укорінення та визначено оптимальні концентрації регуляторів росту для обробки стеблових живців. The aim of this work was to study the effect of growth substances on the rooting of cuttings of evergreen boxwood (Buxus sempervirens L.) in a closed ground, experimentally investigated substances that stimulate root formation and stimulate the growth of roots formed in cuttings of these plants. It is known that at low concentrations will not be stimulatory effect, or it will occur only slightly, while at high – inhibition of growth processes occur that lead to a result contrary to that expected. The results of the study of regenerative capacity of evergreen boxwood in a closed ground, the ways of regeneration of organs in the process of rooting experimentally tested the effect of growth substances on their establishment and the optimal concentration of growth regulators for the treatment of stem cuttings.
Biological Features of Reproduction in Boxwood Evergreen Indoors.
Keywords: регенерація; живцювання; коренеутворення; калюсоутворення; ризогенез; regeneration cuttings; root formation; сallus formation; rhizogenesis